Antidiabetic activity of combined extracts of Hibiscus sabdariffa Linn. and Stevia rebaudiana Bert. on streptozotocin-induced diabetes Wistar rats - Tjitraresmi, Ami; Febriyanti, Raden Maya; Anjabtsawa, Daffa; Susilawati, Yasmiwar; Muhaimin, Muhaimin (Chempublish Journal, 2025)
The increasing prevalence of diabetes mellitus and the limitation in its conventional therapies underscores the need for alternative treatments. Hibiscus sabdariffa Linn. and Stevia rebaudiana Bert. have demonstrated individual antidiabetic activities attributed to their secondary metabolites, including flavonoid and phenolic compounds. This study employed an experimental in vivo design using rats induced with STZ. Thirty rats were divided into five groups (n=6): normal control, negative control, positive control (Glibenclamide), and two treatment groups receiving the combined aqueous extracts of H.sabdariffa and S.rebaudiana (RSAE) at 500 and 1000 mg/kgBW. Diabetes was induced using STZ (50 mg/kgBW administered i.p). Blood glucose levels were measured fasting and 2 hr postprandial at days 0, 3, and 14 after administration of RSAE. Data were analyzed using One-Way ANOVA. RSAE exhibited dose‐dependent hypoglycaemic activity in STZ‐induced diabetic rats, significantly reducing (p < .005) fasting blood glucose by up to 50.7 % and two‐hour post‐prandial glucose by 44.97% at 1000 mg/kgBW.